THE INFLUENCE OF TAX KNOWLEDGE, TAX BREVET TRAINING, AND TRI-NGA IMPLEMENTATION ON CAREER IN THE TAXATION FIELD - Sri Lestari Yuli Prastyatini; Umi Wahidah; Yhoga Heru Pratama; Enggar Kartika Cahyaning; Devi Triani (JEMMA (Journal of Economic, Management and Accounting), 2024)
This study aims to prove the influence of Tax Knowledge, Tax Brevet Training, Tri-Nga Implementation on the Career Interest in Taxation Field. The study used a sample of Universitas Sarjanawiyata Tamansiswa Accounting students class of 2019, 2020, 2021, and 2022. Based on the questionnaires through a google form link to undergraduate accounting students on Universitas Sarjanawiyata Tamansiswa. Sampling technique employed in this study is the purposive sampling the total 119 respondents from the 2019-2022, which were then analyzed using SPSS version 20. Data processing is performed using multiple linear regression analysis. The findings reveal that Tax Knowledge, Tax Brevet Training, Tri-Nga Implementation has a positive effect on the Career Interest in Taxation Field. The variables of taxation knowledge, tax brevet training, and Tri-Nga implementation collectively influence the career interest of accounting students in the field of taxation.